Amine‐Functionalized Carbon Nanodot Electrocatalysts Converting Carbon Dioxide to Methane. Issue 2 (22nd October 2021) - Yadav, Ram Manohar; Li, Zhengyuan; Zhang, Tianyu; Sahin, Onur; Roy, Soumyabrata; Gao, Guanhui; Guo, Huazhang; Vajtai, Robert; Wang, Liang; Ajayan, Pulickel M.; Wu, Jingjie
Abstract: The electrochemical conversion of carbon dioxide (CO2 ) to methane (CH4 ), which can be used not only as fuel but also as a hydrogen carrier, has drawn great attention for use in supporting carbon capture and utilization. The design of active and selective electrocatalysts with exceptional CO2 ‐to‐CH4 conversion efficiency is highly desirable; however, it remains a challenge. Here a molecular tuning strategy−in situ amine functionalization of nitrogen‐doped graphene quantum dots (GQDs) for highly efficient CO2 ‐to‐CH4 conversion is presented. Amine functionalized nitrogen‐doped GQDs achieve a CH4 Faradic efficiency (FE) of 63% and 46%, respectively, at CH4 partial current densities of 170 and 258 mA cm −2, approximating to or even outperforming state‐of‐the‐art Cu‐based electrocatalysts. These GQDs also convert CO2 to C2 products mainly including C2 H4 and C2 H5 OH with a maximum FE of ≈10%. A systematic analysis reveals that the CH4 yield varies linearly with amine group content, whereas the C2 production rate is positively dependent on pyridinic N dopant content. This work provides insight into the rational design of carbon catalysts with CO2 ‐to‐CH4 conversion efficiency at the industrially relevant level. Abstract : The in situ amine functionalization is a general strategy that can be applied to nanoscale carbon catalysts, i.e., in the form of graphene quantum dots (GQDs) regardless of their crystal structure, to promote the selectivity and production rate of CH4 in CO2 electroreduction. Specifically, amine functionalized nitrogen‐doped GQDs achieve CH4 Faradaic efficiency and partial current density of industrial relevance.